Potential of Academic Sociologists & The Way to Tap it in Pakistani Universities - Sadia Jamil; Imran Sabir; Abida Sharif (ASIAN Journal of International Peace & Security (AJIPS), 2022)
Present research endeavors to initiate a discussion on the challenging role of an academic sociologist in Pakistani academia. The study aims to classify the hurdles faced by the academic sociologists within academic environment in Pakistan. This research seeks to highlight the role and responsibilities of a sociologist in developing sociological thought among sociology students in Pakistani universities. We employed qualitative research methods, and conducted six semi-structured interviews with Pakistani academic sociologists, teaching at both private and public universities of the capital city of Pakistan. Research findings indicate that the sociologists are, usually, entangled in pedagogical and bureaucratic challenges, academic ritualism and are less engaged in indigenous epistemic sociology. The study also points out the dormant status of Pakistan Sociological Association (PSA), which is consequential for aggravating the challenges faced by Pakistani academic sociologists. It suggests Higher Education Commission (HEC)’s intervention, and PSA’s revival to play a proactive role by providing indigenous academic platform for making Pakistani sociologists academically more productive and socially more relevant.